Association Between Tobacco Smoking and Dental Caries in the Indonesian Population: Results of a National Study in 2018 - Lelly Andayasari; Rofingatul Mubasyiroh; Iin Nurlinawati; Irna Sufiawati (Korean Society for Preventive Medicine, 2023)
Objectives The 2018 Basic Health Research (RISKESDAS), conducted by the Ministry of Health of the Republic of Indonesia showed a high prevalence of dental caries (88.8%) in Indonesia and suggested that smoking tobacco was associated with an increased risk of dental caries. This study analyzed the association between tobacco smoking and dental caries in the Indonesian population. Methods This was a cross-sectional analysis of secondary data collected from RISKESDAS 2018. The study population included 35 391 Indonesians aged ≥10 years from all 34 provinces. The decayed, missing, and filled teeth (DMFT) index was used to measure dental caries. Smoking status was assessed qualitatively based on smoking activity, and the level of smoking exposure was assessed based on the Brinkman index. A multivariable logistic regression analysis was employed to examine the relationships of smoking status and smoking exposure levels with the DMFT index. Results Of the population aged ≥10 years, 36% had a DMFT≥8 (females: 37.5%, males: 33.9%). Almost one-fourth (23.4%) were current smokers, and 4.1% were ex-smokers. Furthermore, 26.4% had a Brinkman index ≥400, indicating heavy smoking. According to the multivariate analysis, current smoking status was associated with the risk of DMFT≥8 in males (adjusted odds ratio [aOR], 1.40; 95% CI, 1.27 to 1.55; p<0.001) and overall (aOR, 1.07; 95% CI, 1.00 to 1.14; p=0.037). In females, ex-smoking was associated with a 41% higher risk of DMFT≥8 (aOR, 1.41; 95% CI, 1.07 to 1.84; p=0.014). Heavy smoking was associated with a higher risk of DMFT≥8 in males (aOR, 1.38; 95% CI, 1.25 to 1.52; p<0.001) and females (aOR, 1.24; 95% CI, 1.03 to 1.50; p=0.022). Conclusions Tobacco smoking was associated with dental caries in the Indonesian population.